Ureteral Stent Placement Using a Double J-Catheter in the Treatment of Ectopic Ureter in a Dog - Sembenelli, Guilherme; Costa Junior, Jose Sergio; Wittmaack, Monica Carolina Nery; Montanhim, Gabriel Luiz; Dias, Luis Gustavo Gosuen Gonçalves; Moraes, Paola de Castro (Acta Scientiae Veterinariae, 2020)
Background: Ectopic ureter is a congenital anomaly in which the final segment of one or both ureteral orifices is located distal to the bladder trigone. It may be classified as intra- or extramural. Surgical treatment of ectopic ureters in dogs is recommended and the approach varies with the classification. In the postoperative period, complications are common. When stenosis of the new ureteral ostium occurs, immediate repeated surgery is recommended. This study aimed at using the double J catheter placement following neoureterostomy to treat urethral obstruction secondary to the surgical treatment of an intramural ectopic ureter in a dog. Case: An 8-month-old female French bulldog with dysuria and urinary incontinence was seen at a private veterinary hospital in Jaboticabal, São Paulo. The patient had previously been diagnosed with an intramural ectopic ureter on the right side following imaging tests (ultrasound, computed tomography, and abdominal radiography, excretory urography) and had undergone neoureterostomy and closure of the intramural pathway approximately a year ago. Ultrasonographic examination showed dilation of the caudal portion of the ureter and hydroureter, which was suggestive of right ureteral stenosis. Computed tomography was also performed to evaluate the kidneys, ureters, and bladder; an increase in the diameter of the right ureter in its middle portion and close to the bladder triangle was observed. A new surgical intervention was indicated and performed. The ureteral route was identified in a region of the bladder trigone, incised, and probed with a urethral probe No. 04. The intramural course in the proximal urethra was identified and probed with a 16G epidural catheter. It was necessary to perform a neoureterostomy. A longitudinal incision (spatulation) of approximately 5 mm was made in the distal portion of the right ureter to increase the circumference of the anastomosis. The double J 4.7 French (Fr) catheter was inserted through the new ureter ostium into the bladder and advanced into the right kidney in a retrograde manner. Once the proximal end of the double J catheter reached the renal pelvis, the guidewire was withdrawn slowly to allow the catheter to bend in the areas of the renal pelvis and the trigone. The distal end of the double J catheter that extended beyond the bladder lumen was sectioned for better bladder closure. The patient underwent clinical evaluation and laboratory tests (complete blood count and serum creatinine concentration, urine test with bacteriological culture and susceptibility test) 2 weeks after the procedure and, subsequently, every 3 months. Ultrasonography of the urinary tract was performed every 2 months. Discussion: We used a double J catheter in the patient due to a previous obstruction of the ureter ostium after the first surgical procedure. In this way, complications such as postoperative obstructions due to ureteritis and ureteral constriction were avoided and ureteral anastomosis was facilitated. It has been reported that animals subjected to ureteral stent placement have high incidences of dysuria and urinary tract infection, and low incidences of stent migration and occlusion. In this case, no signs of occlusion or obstruction of the implant were identified, but there was a recurrence of urinary tract infections. These frequently cause urethral obstruction associated with the healing of the new ureteral ostium. Patient follow-up and findings associated with the long-term insertion of the double J catheter provide support for the clinical relevance of the present report.